2020
DOI: 10.1515/nanoph-2020-0105
|View full text |Cite
|
Sign up to set email alerts
|

3D super-resolved imaging in live cells using sub-diffractive plasmonic localization of hybrid nanopillar arrays

Abstract: AbstractAnalysing dynamics of a single biomolecule using high-resolution imaging techniques has been had significant attentions to understand complex biological system. Among the many approaches, vertical nanopillar arrays in contact with the inside of cells have been reported as a one of useful imaging applications since an observation volume can be confined down to few-tens nanometre theoretically. However, the nanopillars experimentally are not able to obtain super-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In numerous studies, the combination of dry etching methods with different masking techniques has been utilized for the production of nanoparticles, particularly in materials such as Si, SiN, SiO 2 , and sapphire substrates. To fabricate nanoparticles, various nanosized masks are created on a substrate using lithography techniques such as electron-beam lithography [43][44][45] and microsphere lithography [46][47][48][49]. Following this, dry etching using gases and reactive-ion etching (RIE) is carried out.…”
Section: Etching Based On Semiconductor Fabrication Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…In numerous studies, the combination of dry etching methods with different masking techniques has been utilized for the production of nanoparticles, particularly in materials such as Si, SiN, SiO 2 , and sapphire substrates. To fabricate nanoparticles, various nanosized masks are created on a substrate using lithography techniques such as electron-beam lithography [43][44][45] and microsphere lithography [46][47][48][49]. Following this, dry etching using gases and reactive-ion etching (RIE) is carried out.…”
Section: Etching Based On Semiconductor Fabrication Processesmentioning
confidence: 99%
“…However, the fabricated structure's aspect ratio is limited, and the output of the process depends on the gas used during the process. Kim et al [43] reported the formation of NPs in thin quartz films. In their experiments, they used electron-beam lithography and RIE (Figure 1).…”
Section: Etching Based On Semiconductor Fabrication Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanowires, moreover, support resonant optical modes which can be tailored and enhanced in order to modulate the reflectance, absorbance and transmittance properties of the arrays [ 9 , 13 , 15 , 34 , 35 ]. Nanowire arrays also provide a large surface-to-volume area, beneficial in all the applications based on surface interactions mechanisms, such as sensing [ 36 ], photodetection [ 37 ], and batteries electrodes [ 38 ], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, artificial calibrated arrangements of vertically aligned dielectric quasi one-dimensional structures, shaped as nanowires (NWs), provide ideal platforms to control photonic bandgap materials [13][14][15][16][17][18][19][20][21][22], and more in general are of considerable importance for building-blocks promising for next-generation sensing devices [23]. Indeed, arrays of vertically aligned one-dimensional NWs have demonstrated great potential in photonic applications due to their ability to tightly confine optical signals and to the possibility to easily adjust the growth parameters in order to tune the assemblies' optical properties during the growth [24].…”
Section: Introductionmentioning
confidence: 99%